The discursive representation of host locations in a sports media event: Locating the 'Real Site' of Formula One. Issue 2 (1st June 2014) - Evans, Claire
Locations are often chosen to host major sporting events because of their world and economic status, whilst the hosting of a major sporting event further enhances the standing of a host-location on a global scale. The media play a central role in depicting the image and values of the host-destinations on display, but unlike other major sporting events, such as the World Cup or the Olympic Games that travel to a different destination every four years, the FIA Formula One World Championship travels to multiple worldwide destinations in the course of a season.  Live broadcasts routinely represent both traditional and modern Formula One venues to viewers; especially during programme openings, where they are aligned to: the local, unique characteristics of the destinations travelled to; the global ethos of the sport; and the media context itself.  Using illustrative examples from British broadcasts of Formula One, I explain why delineating the 'core' and 'periphery' of a sports media event is questionable, but although it throws doubt on our ability to pinpoint the 'real site' of a global sports event, it nevertheless illustrates the position that sports, host-locations and the media have as part of a global network.